Community Readiness for Drug Abuse Prevention in Two Rural Communities in Enugu State, Nigeria - Evelyn N. Nwagu PhD, MEd, BSc, RM, RN; Samuel I. C. Dibia PhD, MEd, BSc; Amelia N. Odo PhD, MEd, BSc, HND, RM, RN (SAGE Publishing, 2020)
Background Drug abuse is an issue that affects all people regardless of gender, race, ethnicity, age, or socioeconomic status. It is associated with a range of physical, social, and economic consequences at both individual and community levels. Community involvement is necessary for effective drug abuse prevention. Communities need to be ready for such involvement. Methods We applied the Community Readiness Model and its assessment tool to determine the level of readiness for prevention of drug abuse in Obukpa and Ubollo communities of Nsukka and Udenu Local Government Areas of Enugu North Senatorial zone, Nigeria. Community Readiness Model and the Tool are very useful in identifying gaps in community readiness and capacity as well as guiding strategies for community initiatives. Twelve key informant interviews were conducted and analyzed according to procedures outlined in the Community Readiness handbook. Results The results of the study showed that members of Obukpa and Ubollo communities were at the vague awareness stage. SWOT analysis of the qualitative data revealed the strengths, weaknesses, opportunities and threats within the communities for an intended intervention to increase level of readiness. One such strength is the church, which was identified as a viable means of disseminating information on drug abuse prevention in both communities. Conclusion Rural communities are vulnerable to drug-related problems as a result of low levels of awareness of the dangers of drug abuse. The findings of this study provided strategies and directions for future intervention programmes in the study area. Nurses and other health personnel involved in Community Health Education should take cognizance of the strengths, weaknesses and opportunities within the communities in designing drug abuse prevention intervention programmes.